Islam and global dialogue religious pluralism and the pursuit of peace - Boase, Roger (Ashgate Pub., 2005)
At a time when the world is becoming increasingly interdependent, multi-cultural and multi-religious, the concept of religious pluralism is under assault as a result of hatred, prejudice and misunderstanding from both religious exclusivists and dogmatic secularists." "In this important and timely book, twenty internationally acclaimed scholars and leading religious thinkers respond to contemporary challenges in different ways. Some discuss the idea of a dialogue of civilisations; others explore the interfaith principles and ethical resources of their own spiritual traditions.